IMPROVING STUDENTS’ SPEAKING SKILL THROUGH STORYTELLING OF NARRATIVE TEXT AT GRADE VIII-A OF SMPN I TEMPULING INDRAGIRI HILIR - Lia Diana (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The study purposed to determine if storytelling technique can improve the students’ speaking skill of narrative texts, and the influencing factors of its improvement. It was designed as Classroom Action Research which was conducted in two cycles. Each cycle comprised of five meetings that covered plan, action, observation, and reflection. The research participants were the students of VIII-A SMPN 1 Tempuling Kab. Indragiri Hilir. There were 13 students. The data were collected through (1) observation sheets; students, teacher, teaching steps, (2) field notes, (3) interview, and (4) speaking skill. The research determined that storytelling technique could improve the students’ speaking skill of narrative texts. The factors that influenced its improvement were (a) teaching material, (b) students’ motivation, (c) classroom activities, and (d) teacher’s role.